Assessing Quality and Safety in Pediatric Supracondylar Humerus Fracture Care. Issue 5 (July 2017) - Iobst, Christopher A.; Stillwagon, Matthew; Ryan, Deidre; Shirley, Eric; Frick, Steven L.
Abstract : Background: Recently, there has been an emphasis on improving quality, safety, and value in the delivery of health care in the United States. The American Board of Orthopedic Surgery (ABOS) has developed a performance improvement questionnaire (PIQ) for orthopaedic surgeons managing pediatric supracondylar humerus fracture (PSCHF). Using the supracondylar PIQ as a guide, this study evaluates the process of measuring the outcomes and variations in care to PSCHF patients among pediatric orthopaedic surgeons. Methods: An 88-question survey incorporating the ABOS PIQ was administered to 35 pediatric orthopaedic surgeons at 3 institutions. A retrospective chart review of patients who received operative management of a PSCHF during 2013 was performed. Each of the 17 eligible surgeons supplied 5 patients for a total of 85 patients. Medical records and radiographic imaging were reviewed using the ABOS PIQ data collection sheet. This data collection sheet encompasses the preoperative assessment, intraoperative treatment and assessment, and clinical and radiographic outcomes of patients with PSCHF. Results: A total of 35 surgeons from 6 hospitals completed the online PSCHF survey. Uniform consensus among all 35 surgeons was identified in 21/79 of the questions (27%). Consensus among surgeons within a hospital group but not with surgeons from the other groups was identified in 39/79 (49%) of the questions. No consensus among the surveyed surgeons could be identified in 19/79 (24%) of the questions. For the 85 PSCHF patients the average age was 6 years, and 37% of fractures were type II, 57% of fractures were type III, and there was 1 flexion type. Ninety percent of the patients received a preoperative dose of antibiotics and the postoperative immobilization placed in the operating room was changed in the clinic before pin removal in 58% of the cases. Pins were removed at 3 weeks in 60%, 4 weeks in 30%, 5 weeks in 7%, and after 5 weeks in 3% of the patients and no malunions occurred. Pin tract infection occurred in 2 patients (2.4%). The procedure time ranged from 13 to 171 minutes, with a median time of 37 minutes. Total anesthesia time ranged from 32 to 233 minutes, with a median of 72 minutes. The number of outpatient follow-up visits ranged from 2 to 7 visits, with a median of 3 visits. The number of postoperative radiographs obtained ranged from 1 to 14, with a median of 3 studies. Four patients (5%) returned to the operating room for a repeat surgery. Conclusions: The survey responses from the surgeons at 6 different hospitals demonstrate that there is still considerable variation in care among surgeons, even for such a routine injury. Our chart review also revealed substantial variation in care with subsequent quality and cost-implications. The variations in operating room time, anesthesiology time, number of postoperative visits, number of radiographs ordered, and the initial intraoperative immobilization, all point to opportunities for standardization and lowering of costs. Level of Evidence: Level IV. Abstract : Supplemental Digital Content is available in the text.